THE USE OF KINSHIP ANALYSIS ON PATERNITY TESTING THROUGH CODIS STR LOCI ‘CSF1PO' AND ‘THO1' - Putri, Dwi Fitrianti Arieza; Yudianto, Ahmad (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: Paternity tests compare a child's DNA pattern with the possible father to examine the DNA heritage in ensuring kinship. If there is no information from the father and mother or the child that can be used as a comparison in the forensic DNA examination process (paternity test), there must be a comparison from a close relative as an alternative to obtain the forensic DNA examination. This experiment's purpose is to analyze the use of kinship analysis in forensic identification especially in a paternity test. Methods: This is a descriptive experiment using a cross-sectional design through locus analysis of DNA forensic examination in paternity test using the kinship analysis through STR CODIS loci: CSF1PO and THO1. The variables of this experiment were ‘locus' as the independent variable and ‘allele number' as the dependent variable. This experiment conducted a paternity tests to 8 samples in which the subjects were siblings; the test was administered on the CSF1PO and TH01 loci. Results: This experiment displayed similar allele numbers on the same locus, both in 50% and 100% allele numbers; the research showed similarity in allele numbers of both siblings of which ¼ were inherited from the parents (for 50% allele number similarity), and ½ were inherited from the parents (for 100% allele number similarity). Conclusion: This proves that a paternity test using siblings as the closest kin (kinship analysis) can be used as an alternative if no comparison is obtained from both the parents.